PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN HEALTH CARE BATAM - Sari, Retno; Syaifullah, Syaifullah (SCIENTIA JOURNAL, 2019)
In this study entitled The Influence of Service Quality and Trust in Satisfaction of Batam Health Care Patients, The purpose of this study was to determine the quality of services implemented by the Tamrin Health Care and Trust Clinic of patients towards the Tamrin Health Care Clinic that was used was using quantitative methods and using questionnaires. Are there any effects of service quality on patient trust and satisfaction. The sampling method in this study is to use probability sampling method, which is a sample lighting technique that provides equal opportunities for each member of the population to be selected as a sample. Thus Service Quality (X1) and Trust (X2) have a positive effect on Patient Satisfaction (Y) at Tamrin Health Care Clinic. That is Service Quality variable (X1) proves with significant value (0,000) <alpha value (0,05) and value so that t count> t table 5,919> 1,9717, Trust variable (X2) is significant (0,006) <alpha value (0,05) ) and value so that t count> t table 2,785> 1,9717, variable Patient Satisfaction (Y) is significant (0,000) <alpha value (0,05) and fcount> f table (32,886> 3,04).